A Língua Portuguesa de Angola: descrição dos processos de formação de palavras com base em textos literários - Lemes, Cinthia Aparecida (2013)
This present assignment is insert on a Research Line of History and Description of Portuguese Language of the research group of PUC-SP. It has as theme the creation process of the words and the neologisms in Angolan Portuguese based on literary texts from the own country, to know: Luandino Vieira (1963), João Melo (2002), Ondjaki (2002). These writers work on a engaged literature and their stories are connected with social context of the country, telling how people passed through the process of Independence from Portugal (1961 -1975), the period after colonization and the Civil War (1975-2002) and how angolans looked for their national identity and started to build a new story for themselves, this time with no war or power competition. In this assignment, it´s discussed the question of multilingualism in Angola and number of ethnic groups with own languages existing in the country and living together, some pacifically and others not that much. The discussion about this theme is relevant because it tries to identify in which aspects the Angolan Portuguese language has its own marks that differentiate it of Portuguese language from Portugal. Many transformations in Portuguese language of Angola were enabled by the resistance to the culture and language model that, until the Independence, Angolans had received from their colonizing. So, insert words, grammatical structures and/or intonation of national languages to Portuguese language meant to turn more national the imposition of an official language. The fact that Angolans agreed with the official language as a goal to keep peace between ethnic groups had not meant each Angolan could not give typical characteristics to the language, turning it more Angolan. What is seen in this paper are descriptions and reflections mixed to analysis about the Angolan variation. The results of the analysis say that a big part of the derivational process of Angolan language were based in the national language quimbundo, with increase of suffixes and desinences (like plural) from Portuguese language; there was also a large number of neologisms of form incidents